Practical classes in the English Language as a means to treat the content that contributes to the professional performance. - Clara Esther Gómez Gonzalvo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
The teaching organizing forms include the conference, the seminar, and the practique lesson. In this moment we are concerned about the practique lesson and specifically of the english language as a means for the dealing with the content through the use of the infered resources accountable to the professional development.